"What the Hell Is This, and Who the Hell Are You?" Role and Identity Negotiation in Research-Practice Partnerships. (May 2019) - Farrell, Caitlin C.; Harrison, Christopher; Coburn, Cynthia E.
In research-practice partnerships (RPPs), the line between researcher and practitioner can be blurred, and the roles for everyone involved may be unclear. Yet little is known about how these roles are negotiated and with what consequences for collaborative efforts. Guided by organizational theory, we share findings from a multiyear case study of one RPP, drawing on observations of partnership leadership meetings and interviews with school district leaders and partners. Role negotiation occurred in more than one third of leadership meetings, as evidenced by identity-referencing discourse. When roles were unclear, collaborative efforts stalled; once partners renegotiated their roles, it changed how they engaged in the work together. Several forces contributed to these dynamics, including the partner's ambitious yet ambiguous identity and the introduction of new members to the group. This study offers implications for those engaged in partnership work and provides a foundation for future research regarding role negotiation in RPPs.